2021
DOI: 10.3390/e23040485
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Discovery for Higher Education Student Retention Based on Data Mining: Machine Learning Algorithms and Case Study in Chile

Abstract: Data mining is employed to extract useful information and to detect patterns from often large data sets, closely related to knowledge discovery in databases and data science. In this investigation, we formulate models based on machine learning algorithms to extract relevant information predicting student retention at various levels, using higher education data and specifying the relevant variables involved in the modeling. Then, we utilize this information to help the process of knowledge discovery. We predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 33 publications
0
46
0
2
Order By: Relevance
“…ML algorithms are widely used for prediction purposes and applied to provide solutions to questions such as global solar radiation [9], accuracy in determining the mortality rate in COVID-19 patients [10], and efficient processes for manufacturing industries [11]. In addition, ML algorithms assist the educational sector to evaluate student performance [12], forecast student dropout rates in any course [13], and understand students' unique learning styles [14]. Due to ML's vast and dynamic implementation and its capability to learn from any dataset, and predict and classify future transactions, we have selected multiple ML algorithms for this study.…”
Section: Introductionmentioning
confidence: 99%
“…ML algorithms are widely used for prediction purposes and applied to provide solutions to questions such as global solar radiation [9], accuracy in determining the mortality rate in COVID-19 patients [10], and efficient processes for manufacturing industries [11]. In addition, ML algorithms assist the educational sector to evaluate student performance [12], forecast student dropout rates in any course [13], and understand students' unique learning styles [14]. Due to ML's vast and dynamic implementation and its capability to learn from any dataset, and predict and classify future transactions, we have selected multiple ML algorithms for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Tables [3][4][5][6][7] show the predictive performance of the seven comparison algorithms in five metrics: AP, RL, HL, CV, and OE, respectively. The symbol ↑ indicates a larger value for better performance; the symbol ↓ indicates a smaller value for better performance.…”
Section: Resultsmentioning
confidence: 99%
“…One of the key indicators of high-level education quality is students' performance in the setting of the learning environment. Studies have shown that the early learning stage of the course is crucial [1][2][3], in which the students are able to nurture their interests in the relevant learning through the understanding and digestion of the syllabus structure and content organization, forming a solid foundation for the subsequent learning stages [4,5]. Adelman et al [6] conducted a long-term and systematic statistical study on behalf of the National Center for Education Statistics in the US, in order to reveal the constellational correlation and significance of the class attainment, attendance, curriculum, and student performance with the elucidation of what, when, where, and how they study.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are an appropriate step to employ in all statistical/econometric modeling. Furthermore, there exists a potential use in machine, deep, and statistical learning models [39,[59][60][61]. Future research will consider other variables and relationships, such as production linkages and employment effects of the COVID-19 pandemic phenomena.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%